A DESCRIPTION OF THE RELATIONSHIP BETWEEN OCCUPATIONAL STRESS AND BLOOD PRESSURE CHANGES IN WORKSHOP MECHANICS - Dadang Shokhibul Kafi; Erwin Dyah Nawawinetu (The Indonesian Journal of Public Health, 2022)
Introduction: Stress is the occurrence of the individual's emotions, thoughts, and physical conditions. Each individual has the potential to experience stress. Stress that comes from the workplace is called occupational stress. Increased blood pressure is one of the physical impacts of work stress that needs attention due to continuous increase in blood pressure will cause high blood in the worker. The purpose of this study was to describe the overview of the relationship between occupational stress and the change in blood pressure on workers. Methods: This was descriptive observational research. Respondents were 30 people (mechanics of the workshop). The variables of this research were occupational stress level and systolic blood pressure changes. The stress level was measured by using a questionnaire, while blood pressure was measured by using the tensimeter. The correlation between stress level and blood pressure was analyzed by using cross-tabulation. Result: The results showed that the percentage of respondents with moderate stress levels was higher (53.4%) compared to mild stress levels (46.6%). The percentage of respondents with increased systolic blood pressure was higher (63.3%) compared to respondents with decreased systolic blood pressure (3.4%) and constant blood pressure (33.3%). The percentage of respondents with increasing blood pressure was higher for those with moderate stress levels (93.7%) compared to those with mild stress levels (28.5%). Conclusion: It can be concluded that the higher the stress level, the higher percentage of respondents with increasing blood pressure would be.